E-grocery challenges and remedies: Global market leaders perspective - Marcia Mkansi; Chukuakadibia Eresia-Eke; Oyetola Emmanuel-Ebikake (Cogent Business & Management, 2018)
The purpose of the study is to identify logistic elements germane to e-grocery businesses, and to reveal the challenges collateral with each logistic element. Further, it strives to create a better understanding of specific remedies that have been employed by top e-grocery retailers to overcome existing challenges while aligning identified challenges with Turban's framework. Extensive semi-structured interviews were conducted with management staff in three of the top ten global online grocery retailers and another that was a market leader in a European country. The qualitative data collected was transcribed and coded using a non-hierarchical axial coding to identify emerging themes in content analysis. The results expose a range of challenges that could be compartmentalised into three broad categories, in harmony with the different stages of the order fulfilment process. Interestingly, the study found that most challenges were operational rather than tactical or strategic in nature. While the study expands existing knowledge, its revelation that most challenges lie in the management of roles and responsibilities domain is instructive. This makes it imperative for practitioners to focus on this specific area if meaningful improvement in e-grocery retailing performance is to be realised. This research offers a systematic understanding of supply and distribution challenges, including remedies utilised to ameliorate the effect of the challenges from the perspectives of the top companies in the industry. These remedies can be invaluable for existing and emerging e-grocers.
Keywords: 650